Antioxidant activity of free and bound phenolics in Curcuma longa - Saroj Yadav; Anoop Kumar (International Journal of Phytomedicine, 2013)
The antioxidant activity of free and bound phenolics of turmeric (Curcuma longa) extract prepared by treating with enzyme and without enzyme was analyzed. The enzyme assisted extraction of Curcuma longa showed higher levels of antioxidant activity as evaluated by both free radical scavenging compared to that of non enzyme extracts. Higher level of antioxidant activity in C. longa has been attributed to the phenolic content in them. The free and bound phenolics of enzyme treated extract of C. longa showed high content of phenolic compounds (31.0 and 1.3 mg/g) compared to that of non enzymatic extract (28.8 and 3.5 mg/g). Our studies clearly suggest the presence of potent antioxidants in C. longa.